Dynamic of Saline Soil Cations after NaCl Application on Rice Growth and Yields - Wanti Mindari; Wuwut Guntoro; Zaenal Kusuma; . Syekhfani (JOURNAL OF TROPICAL SOILS, 2013)
Saline soil cation dynamic is determined by the proportion of salt cations dissolved either acidic or alkaline.  Common base cations in saline soil are in the proportion of  Na >  Ca >  Mg >  K.  They affects the availability of water,  nutrients, and plant growth.  The six level of  NaCl  were 0, 15, 30, 45, 60, and  75 mM  and  two  types of  soil  (saline and non saline) from Gununganyar and Mojokerto were evaluated  to soil sample cations taken from  depth of  0-5, 5-10, 10-15, and 15-20 cm. Rice growth and yields were measured. The experiment indicated  that increasing doses of NaCl increased the soil Na after rice harvest and decreased K, Ca and Mg contents, both of non-saline and saline soil, decreased of rice growth and yield (straw, grain, number of tiller).  NaCl up to 30 mM  caused highest Ca:Mg ratio, about 8, suppressed nutrient available, inhibited root growth and reduced nutrient uptake.Keywords:  Cation dynamic,  NaCl,  rice yield , saline soil[How to Cite: Mindari W, WGuntoro, Z Kusuma and Syekhfani. 2013.Dynamic of Saline Soil Cations after NaCl Application on Rice Growth and Yields. JTrop Soils 18 (3): 185-194. Doi: 10.5400/jts.2013.18.3.185][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.3.185]REFERENCESAkram M, MY Ashraf, R Ahmad, EA Waraich, J Iqbal and M Mohsan. 2010. Screening for salt tolerance in maize (Zea mays L.) hybrids at an early seedling stage. Pakistan J Bot  42: 141-154.Bohn H,  BL McNeal and GA O’Connor. 2001. Soil Chemistry, Third Edition. John Wiley and Sons. Inc. 307p. Carmona FC, I Anghinoni, MJ Holzschuh and MH Andrighetti.  2010.  Cation dynamics in soils with different salinity levels growing irrigated rice. Rev Bras Ciênc Solo 34: 1851-1863. Ching PC and SA Barber. 1979.  Evaluation of temperature effects on K  uptake by corn. Agron J 71: 1040- 1044.da Silva EN, RV Ribeiro, SLF Silva,  RA Viégas and JAG Silveira. 2011. Salt stress induced damages on the photosynthesis of physic nut young plants Sci Agric  68: 62-68.Gacitua M, M  Antilen and M Briceno. 2008. K–Ca–Mg binary cation exchange in saline soils from the north of Chile. Aust J Soil Res 46:  745-750.Junita Y, YK Kazutake and K Takashi. 2005. Application effects of controlled-availability- fertilizer on the dynamics of soil solution composition in the root zone. http://natres.psu.ac.th/Link/SoilCongress/bdd/symp14/2095-t.pdf. Accessed on 20 February 2013.Korb N, C Jones and J Jacobsen. 2005. Secondary  Macronutrients: Cycling, Testing and Fertilizer  Recommendations.  Nutrient Management Module No. 5. Montana state University extension service.16 p. Landon JR. 1984. Booker Tropical Soil Manual. United State of America. Longman, New york, Academic Press. 227 p.Mindari W, Maroeto and Syekhfani. 2009. Efek pemberian air salin rekayasa pada EC tanah dengan amelioran bahan organik. Prosiding  Seminar Nasional Fakultas Pertanian dan LPPM UPN “Veteran“ Jatim, Surabaya (in Indonesian). Nakamura Y, K Tanaka, E Ohta and M Sakata. 1990. Protective effect of external Ca2 on elongation and the intracellular concentration of K   in intact mung bean root under high NaCl stress. Plant Cell Physiol 31:  815-821.Nassem I and HN Bhatti. 2000. Organic Matter and salt concentration effect cation exchange equilibria in non-calcareous soils. Pakistan J  Biol Sci  3: 1110-1112.Nosetto M D, E G Jobba´gy, T To´th and CM Di Bella. 2007. The effects of tree establishment on water and salt dynamics in naturally salt-affected grasslands. Oecologia 152: 695-705.Rachman A, GM Subiksa, D Erfandi  and P Slavich. 2008.  Dynamics of  tsunami-affected soil properties. In: F Agus and G Tinning (eds).  International Workshop on Post Tsunami Soil Management, Bogor, Indonesia, 1-2 July 2008, pp. 51-64.Rengasamy P. 2006. World salinization with emphasis on Australia. J Exp Bot 57: 1017-1023.Shani U and  LM Dudley.  2001. Field Studies of Crop Response to Water and Salt Stress. Soil Sci  Soc    Am J 65: 1522-1528.Slaton NA, D Dunn and B Pugh. 2004.  Potassium nutrition of flood-irrigated rice. Better Crops 88: 20-22Yuniati  R. 2004. Penapisan galur kedelai Glycine Max (L.) Merrill toleran terhadap NaCl untuk penanaman di lahan salin. Makara - Sains 8:  21-24.Zeng L and Shannon MC. 2000. Salinity effects on seedling growth and  yield components of rice. Crop Sci 40:  996-1003.